2019
DOI: 10.6018/analesps.35.3.323151
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment in cybervictims and cyberbullies in secondary education

Abstract: El auge de las agresiones cibernéticas entre estudiantes de secundaria y la importancia de ciertas variables de ajuste psicosocial para la comprensión de este tipo de conducta violenta, tanto en agresores como en víctimas, plantean como objetivo en el presente trabajo analizar el perfil psicosocial de ambos implicados en situaciones de ciberagresión. Las variables de ajuste analizadas fueron autoconcepto, estrés percibido, soledad, sintomatología depresiva, ansiedad social, satisfacción con la vida e inteligen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 41 publications
6
24
0
15
Order By: Relevance
“…Nevertheless, it is known that cybervictimisation [ 21 ] and cyberaggression [ 55 ] are related to lower overall academic performance. Furthermore, it has been observed that there is a relationship between academic performance in physical education with factors such as physical self-concept [ 56 ], which is an element related to cyberbullying in both victims and bullies [ 57 ]. This demonstrates that cyberbullying is a powerful component in lowering general self-image and self-confidence, so physical education and physical activity, as they promote the improvement of physical self-concept [ 58 ], could become protective factors against cyberbullying in both victims and aggressors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is known that cybervictimisation [ 21 ] and cyberaggression [ 55 ] are related to lower overall academic performance. Furthermore, it has been observed that there is a relationship between academic performance in physical education with factors such as physical self-concept [ 56 ], which is an element related to cyberbullying in both victims and bullies [ 57 ]. This demonstrates that cyberbullying is a powerful component in lowering general self-image and self-confidence, so physical education and physical activity, as they promote the improvement of physical self-concept [ 58 ], could become protective factors against cyberbullying in both victims and aggressors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we consider it necessary to develop identity in a tight way in the adolescent stage to avoid this occurring at later educational stages, such as at university, and to continue to address problems in interpersonal relationships and abuse of the internet [ 26 ]. Similarly, it is necessary to promote self-esteem [ 23 ], coping strategies [ 52 ], emotional regulation [ 2 , 4 , 6 , 7 , 8 , 9 , 53 ], skills for conflict resolution and stress management, self-control, social and communication skills, and healthy leisure activities [ 16 , 19 , 20 , 54 ]. The family also has a relevant role to play in preventing internet addiction [ 6 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of such difficulties may be, for example, abdominal pain, headache, sleep disturbances, experiences feelings of shame, sadness, depression, anxiety or his own failure, but also feelings of constant danger. Cyberbullying may result in his complete psychological collapse and, in the worst cases, suicide (Canas, Esteves, Marzo, & Pqueras, 2019).…”
Section: Cyberbullying Among Juvenilesmentioning
confidence: 99%